(3JMOjK GdbjGOI GdEOGQjI hXGFagG HacQ GdEOGQI GdNGUI (B/ s - (3WGQb YHOGdeLjO GdYGjbs; (3GfhQ CMeO QSdGf s; (3LGeYI GdbGgQI s (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3gPG GdHMK jWQM HYV GdCacGQ GdJi bO JYGhf ai JMOjK GdbjGOI GdEOGQjI hjbhe Ydi KdGKI eMGhQ GdChd jJYdb HGdehGFeI GdJTQjYjI hZQS GdKbGaI GdEjLGHjI jWQM HYV GdJYOjdGJ ddbGfhf GdMGdi Qbe (B5 (3dSfI (B1991 (3hdGFMJg GdJfajPjI GdeJYdbI HTZd GdhXGFa GdbjGOjI CeG GdeMhQ GdKGfi ajJYdb HGdYfGjI HGdefXheI GdJOQjHjI hGdJfejI GdEOGQjI ddfghV HCOGA GdbjGOGJ jJfGhd WQb hhSGFd GdJOQjH HGdeSJbHd CeG GdeMhQ GdKGdK ajYJeO Ydi COGA hXGFa GdbjGOI HGdESJYGfI HacQ GdEOGQI GdNGUI ef MjK GdeQhfI hGdYde hESJNOGe GdhSGFd GdYdejIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B159-160s
Keywords: (3GdbGfhf GdYGes; (3GdGOGQI GdYGeIs; (3GdbjGOI GdEOGQjI s; (3acQ GdEOGQI GdNGUIs; (3GdHjQhbQGWjIs; (3GdJfXje hGdJhLjgs; (3GdbjGOI GdGOGQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes